Natural-Based Biomaterials for Peripheral Nerve Injury Repair - Fornasari, Benedetta E.; Carta, Giacomo; Gambarotta, Giovanna; Raimondo, Stefania (Frontiers in Bioengineering and Biotechnology, 2020)
Peripheral nerve injury treatment is a relevant problem because of nerve lesion high incidence and because of unsatisfactory regeneration after severe injuries, thus resulting in a reduced patient’s life quality. To repair severe nerve injuries characterized by substance loss and to improve the regeneration outcome at both motor and sensory level, different strategies have been investigated. Although autograft remains the gold standard technique, a growing number of research articles concerning nerve conduit use has been reported in the last years. Nerve conduits aim to overcome autograft disadvantages, but they must satisfy some requirements to be suitable for nerve repair. A universal ideal conduit does not exist, since conduit properties have to be evaluated case by case; nevertheless, because of their high biocompatibility and biodegradability, natural-based biomaterials have great potentiality to be used to produce nerve guides. Although they share many characteristics with synthetic biomaterials, natural-based biomaterials should also be preferable because of their extraction sources; indeed, these biomaterials are obtained from different renewable sources or food waste, thus reducing environmental impact and enhancing sustainability in comparison to synthetic ones. This review reports the strengths and weaknesses of natural-based biomaterials used for manufacturing peripheral nerve conduits, analyzing the interactions between natural-based biomaterials and biological environment. Particular attention was paid to the description of the preclinical outcome of nerve regeneration in injury repaired with the different natural-based conduits.